Evidence Searches Undertaken by Knowledge and Library Specialists Save the Time of Health Care Professionals and Produce an Economic Benefit to the NHS in England. Issue 4 (2nd October 2022) - Edwards, Clare; Gilroy, Dominic; Mallender, Jacque
ABSTRACT: Busy health-care professionals have a duty to apply the evidence base to practice and decision-making. Health-care knowledge and library specialists have the skills to provide efficient and effective evidence searches. To identify the advantages and cost benefits associated with knowledge and library specialists undertaking evidence searches on behalf of health-care professionals, evidence from a literature review was combined with impact case studies of evidence searches in NHS Knowledge and Library Services, identifying time savings and cost benefits. The cost-effectiveness ratio for knowledge specialists delivering evidence searching services was identified as 1:3.85 with the current net benefit to the NHS in England estimated at £37 million (42 million U.S. dollars). A range of additional benefits are also generated through using knowledge and library specialists. Greater investment in these specialists would ensure accelerated access to better quality evidence and maximum benefit across health-care systems.